ENHANCING PRONUNCIATION SKILLS THROUGH PHONETIC SYMBOLS: A CASE STUDY AT THE ENGLISH COURSE IN SIDRAP - Roni, Roni; Ibrahim, Ibrahim; Sunandar, Sunandar; Andang, Baharuddin (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study explores the effectiveness of teaching pronunciation through phonetic symbols at The English Course in Sidrap. The research aims to describe the instructional process, assess student responses, and identify tutor strategies for overcoming pronunciation challenges. A qualitative descriptive approach was employed, using interviews, observations, documentation, and questionnaires for data collection. The findings reveal that the course utilized a direct method combined with a reading aloud technique, supported by tools such as whiteboards, speakers, Oxford dictionaries, and module books. Students faced challenges with mother tongue interference, particularly in distinguishing vowel sounds. However, the incorporation of phonetic symbols, motivational strategies, and interactive techniques, such as songs, contributed to a positive learning experience. Tutors addressed difficulties by providing additional support materials and motivational strategies. The study concludes that teaching pronunciation using phonetic symbols can significantly improve learners' pronunciation skills when combined with engaging teaching strategies and continuous evaluation.